Herbert H. Golden and Seymour O. Simches, Modern Iberian language and literature: A bibliography of homage studies. Harvard University Press, Cambridge, Mass., 1958; x + 184 pp. - Gilman, Stephen (Nueva Revista de Filología Hispánica (NRFH), 1962)
Se reseñó el libro: Modern Iberian language and literature: A bibliography of homage studies.